Competition and Chaos : U.S. Telecommunications since the 1996 Telecom Act - Crandall, Robert W. (Book collections on Project MUSE., 2005)
"Examines how the 1996 Telecommunications Act and its antecedents have affected the major telecommunications providers and analyzes the act's effect on economic welfare in the United States"--Provided by publisher.